REAL-TIME ELASTOGRAPHY AND ITS CLINICAL APPLICATION COMPARED WITH OTHER METHODS FOR EVALUATION OF THE LIVER FIBROSIS DEGREE IN PATIENTS WITH CHRONIC HEPATITIS C - M. A. Belopolskaya; V. Yu. Avrutin; O. D. Denisova; E. V. Lichnaya; E. Yu. Yushina; S. I. Gurina; A. V. Dmitriev; A. A. Yakovlev (Журнал инфектологии)
In this work we investigated to which extent the evaluation results of the degree of hepatic fibrosis obtained by realtime elastography (RTE) method are compatible with the results of the transient elastography (TE) and with the APRI indexes. We also analyzed the factors which can influence the reliability of the fibrosis degree evaluation obtained by different methods.Materials and methods. The study included 99 patients (60 women and 39 men) with HCV, examined in the polyclinic department of the Saint-Petersburg Botkin clinical infectious hospital in 2017. In 83 patients, the fibrosis degree in the liver tissue has been evaluated by the RTE method using HI VISION Preirus (Hitachi, Japan) with a linear sensor. In 67 patients, the evaluation has been performed by the TE method using Fibroscan (Echosens, France). Both methods have been applied to 51 patients.Conclusions. The aplication results of the RTE and TE methods do not differ significantly for patients with a severe fibrosis. Usually, the degree of fibrosis in patients with CHC obtained by the RTE is higher than the one obtained by the TE in the same patient. Due to the possibility to visualize a larger area under study, the RTE method has clear advantages in evaluating the degree of fibrosis in liver tissue in patients with focal changes in the liver. If the results obtained by the RTE and TE methods differ significantly, alternative methods must be used, such as a liver biopsy and biochemical methods.